2000
DOI: 10.1523/jneurosci.20-22-08559.2000
|View full text |Cite
|
Sign up to set email alerts
|

Firing Patterns and Correlations of Spontaneous Discharge of Pallidal Neurons in the Normal and the Tremulous 1-Methyl-4-Phenyl-1,2,3,6-Tetrahydropyridine Vervet Model of Parkinsonism

Abstract: To investigate the role of the basal ganglia in parkinsonian tremor, we recorded hand tremor and simultaneous activity of several neurons in the external and internal segments of the globus pallidus (GPe and GPi) in two vervet monkeys, before and after systemic treatment with 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) and development of parkinsonism with tremor of 5 and 11 Hz.In healthy monkeys, only 11% (20/174) of the GPe cells and 3% (1/29) of the GPi cells displayed significant 3-19 Hz oscillation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

48
443
7

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 535 publications
(498 citation statements)
references
References 56 publications
48
443
7
Order By: Relevance
“…While our focus is on modulation of thalamic firing by GPi, the interacting STN and GPe network is crucial in our model in that its signals (both from STN to GPi and from GPe to GPi) interact with intrinsic GPi currents to generate patterns of of GPi activity that are consistent with experimental data (DeLong, 1971;Filion and Tremblay, 1991;Wichmann et al, 1999;Raz et al, 2000;Hashimoto et al, 2003). We assume that the thalamus receives two sources of input.…”
Section: The Goal Of This Paper Is To Demonstrate With a Computationmentioning
confidence: 95%
See 3 more Smart Citations
“…While our focus is on modulation of thalamic firing by GPi, the interacting STN and GPe network is crucial in our model in that its signals (both from STN to GPi and from GPe to GPi) interact with intrinsic GPi currents to generate patterns of of GPi activity that are consistent with experimental data (DeLong, 1971;Filion and Tremblay, 1991;Wichmann et al, 1999;Raz et al, 2000;Hashimoto et al, 2003). We assume that the thalamus receives two sources of input.…”
Section: The Goal Of This Paper Is To Demonstrate With a Computationmentioning
confidence: 95%
“…Several authors have pointed out that the pattern of neuronal activity, not just the rate, may be important (Bergman et al, 1994;Nini et al, 1995;Magnin et al, 2000;Montgomery et al, 2000;Obeso et al, 2000;Raz et al, 2000;Brown et al, 2001;Terman et al, 2001Terman et al, , 2002. In particular, numerous experimental studies have demonstrated that neurons within both the STN and GPi show an increased level of synchrony and bursting activity during parkinsonian states (Bergman et al, 1994;Nini et al, 1995;Magnin et al, 2000;Raz et al, 2000;Brown et al, 2001). Using a computational model, we show that while synchronous and patterned output of GPi (corresponding to a parkinsonian state) may disrupt the thalamic ability to relay depolarizing (e.g., sensorimotor) inputs, high-frequency, tonic output of GPi (corresponding to DBS) may restore thalamic relay capabilities.…”
Section: The Goal Of This Paper Is To Demonstrate With a Computationmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of DBS electrodes for recording purposes in humans, and in a large number of animal studies [44,152,[322][323][324][325][326], has emphasized that many of the identified electrical disease markers (e.g., oscillatory bursting or phase-amplitude coupling) can be explained by an abnormal level of synchronous neuronal discharge that may ultimately result in increased beta-band oscillations throughout the corticobasal ganglia circuits. Studies in the normal basal ganglia have shown that neighboring neurons tend to fire independently (e.g., [44,45]), perhaps continuing at the cellular level what is readily apparent as circuit segregation at the macroanatomic level [8,10].…”
Section: Abnormal Levels Of Synchrony May Be a Fundamental Electrophymentioning
confidence: 99%